2014
DOI: 10.1186/s12866-014-0316-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the human saliva microbiome from different climate zones: Alaska, Germany, and Africa

Abstract: BackgroundAlthough the importance of the human oral microbiome for health and disease is increasingly recognized, variation in the composition of the oral microbiome across different climates and geographic regions is largely unexplored.ResultsHere we analyze the saliva microbiome from native Alaskans (76 individuals from 4 populations), Germans (10 individuals from 1 population), and Africans (66 individuals from 3 populations) based on next-generation sequencing of partial 16S rRNA gene sequences. After qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
160
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(178 citation statements)
references
References 56 publications
(63 reference statements)
14
160
3
1
Order By: Relevance
“…It is becoming increasingly recognized that there is a high degree of variation in the oral microbiome between different ethnic and geographical populations and between individuals within these populations . The present study has extended these observations and has shown considerable volatility in four species of subgingival bacteria over a 5‐year period using a previously described, highly sensitive, qPCR technique in a defined population of patients with CVD.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It is becoming increasingly recognized that there is a high degree of variation in the oral microbiome between different ethnic and geographical populations and between individuals within these populations . The present study has extended these observations and has shown considerable volatility in four species of subgingival bacteria over a 5‐year period using a previously described, highly sensitive, qPCR technique in a defined population of patients with CVD.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have shown that up to 78% of the normal general population may carry A. actinomycetemcomitans , irrespective of their periodontal disease status , such that the higher prevalence seen in the present study may reflect the more sensitive technique, differences in the population per se, or both. Indeed, a recent study has demonstrated a high degree of variation in the oral microbiome between different population groups, as well as both intra‐individual and inter‐individual diversity . All patients in the current study had a history of CVD and as such consisted largely of older men and thus represent a different population from the general populations studied previously.…”
Section: Discussionmentioning
confidence: 78%
“…However, several studies have demonstrated that there may be racial differences in the microbiome of different human habitats, including the oral cavity. 43 Hence, the differential associations among African-Americans and European-Americans in our study may be also derived from the racial differences in oral microbiome. For example, despite the smaller sample size of European-Americans, associations of the genus Lautropia and the species Lactobacillus salivarius with CRC risk were stronger among European-Americans than among African-Americans.…”
Section: Discussionmentioning
confidence: 75%
“…Lassalle et al 33 observed a higher saliva microbiome diversity in rural Philippines than in the urban US, and Nasidze et al 34 found a higher diversity in rural hunter-gatherers from Uganda than in urban individuals from Sierra Leone and DRC, both of which are consistent with the results from the gut. However, African populations were characterized by a less diverse saliva microbiome than rural individuals from Alaska or urban individuals from Germany 35 , thus opposite to the trends observed for the gut microbiome. Similarly, the saliva microbiome of Native Americans in Oklahoma had lower diversity than the microbiome of neighbouring more urbanized individuals of European descent 36 .…”
mentioning
confidence: 69%